The effectiveness of using quartet cards to improve students' vocabulary skills at Madrasah Ibtidaiyyah Al Hanif in Palu City - Jumahir, Al Magfira; Abidin, Munirul (IAIN Datuk Laksemana Bengkalis, Indonesia, 2025)
This study aims to determine the effectiveness of using quartet cards in improving the mufrodat (Arabic vocabulary) skills of fourth-grade students at Madrasah Ibtidaiyyah Al Hanif in Palu City. The method used was a quasi-experimental design with a pretest-posttest control group. The research subjects were 40 students divided into two groups: an experimental group using quartet cards and a control group using conventional methods. Data collection was conducted through vocabulary tests before and after the intervention. The results showed a significant improvement in vocabulary mastery in the experimental group compared to the control group. The average post-test scores of the experimental group were statistically higher, proving that quartet cards are effective as a learning aid for Arabic vocabulary. This study suggests that Arabic language teachers at the elementary level should maximize the use of interactive media such as quartet cards in the learning process